REFLECTION OF THE DIGITAL TRANSFORMATION ON TOURIST TYPOLOGY: VIRTUAL TOURIST - GÜNCAN , Özlem (SSD Journal, 2021)
With the beginning of the Industrial Revolution in the 18th century, the world entered a digital transformation process and societies were closely affected by this transformation. One of the areas affected by the digital transformation has been tourism, and this transformation has caused the tourism activities of the tourists and the tourism experience they gained to be transferred to the digital world. This situation has also changed tourist practices and eliminated the need for tourists to travel far from their homes in order to participate in tourism. All these developments in the field of tourism have brought the consepts of virtual tourism and virtual tourist to the agenda. In this study, which is prepared from this point, it is aimed to introduce the concept of a virtual tourist to the literature, based on the reflections of the digital transformation in tourism on tourist experiences. In this context, this study has been conducted from a conceptual point of view, and the data have been obtained by reviewing the literature. Reviewing has been carried out in the context of the concept of digital transformation, the digital transformation process in tourism and the virtual tourism experience. The data obtained from reviewing have been evaluated with a holistic approach. At the end of the study, it has been suggested to use the concept of virtual tourist for the virtual tourism participant in the literature and a definition trial has been made for this concept.